LANDSLIDES MECHANISM ANALYSIS AT KM 258 PONOROGO AT PACITAN ROAD - Miftahul Avidatur Rohmah; Arief Rachmansyah; Harimurti Harimurti (Rekayasa Sipil, 2022)
One of the locations where landslides occurred on the Pacitan - Ponorogo route was at KM 258 in December 2017. At that location there are 3 adjacent slope segments, the first segment and the second segment had landslides, to prevent landslide at the third segment investigation was carried out on  the slope. Kinematics analysis method was used using the DIPS program to determine the slope failure type and to obtain the circular failure type. The weighting of RMR rock mass on the slopes studied obtained value of 52 (class III) where the rock type is moderate, and the correlation with the SMR on class III RMR rocks is the recommended slope angle of 55°. After slope stability simulation at angles of 80°, 75°, 70°, 65°, 60° to 55°, the effective angle is 70° with an FS value of 1.6.